Towards a more realistic, cost effective and greener ground movement through active routing: a multi-objective shortest path approach - Chen, Jun; Weiszer, Michal; Locatelli, Giorgio; Ravizza, Stefan; Atkin, Jason A.; Stewart, Paul; Burke, Edmund (Institute of Electrical and Electronics Engineers, 2016)
Based on the multi-objective optimal speed profile generation framework for unimpeded taxiing aircraft presented in the precursor paper, this paper deals with how to seamlessly integrate such optimal speed profiles into a holistic decision making framework. The availability of a set of non-dominated unimpeded speed profiles for each taxiway segment with respect to conflicting objectives can significantly change the current airport ground movement research. More specifically, the routing and scheduling function that was previously based on distance, emphasizing time efficiency, could now be based on richer information embedded within speed profiles, such as the taxiing times along segments, the corresponding fuel consumption, and the associated economic implications. The economic implications are exploited over a day of operation to take into account cost differences between busier and quieter times of the airport. Therefore, the most cost-effective and tailored decision can be made, respecting the environmental impact. Preliminary results based on the proposed approach are promising and show a 9%–50% reduction in time and fuel respectively for two international airports, viz. Zurich and Manchester Airports. The study also suggests that, if the average power setting during the acceleration phase could be lifted from the level suggested by the International Civil Aviation Organization (ICAO), ground operations may achieve the best of both worlds, simultaneously improving both time and fuel efficiency. Now might be the time to move away from the conventional distance based routing and scheduling to a more comprehensive framework, capturing the multi-facetted needs of all stakeholders involved in airport ground operations.